Coping differences between generations of Italo-Canadians during a Crisis of Meaning - Castelli, Samantha (Université d'Ottawa | University of Ottawa, 2025)
Immigrants from all over have made the choice of leaving behind familiar and perhaps difficult circumstances in their country of origin for promises of change, economic opportunity, and long-term stability in new and foreign places. However, immigration does not come without its changes to both the immigrant and their greater environment. In the case of Italian immigrants to Canada, immigrants were shaped by the Canadian cultural landscape and the Canadian context then went on to be shaped by these very same immigrants. Over time, as Italian immigrants settled down and began to build their own families, subsequent generations found themselves navigating a dual culture. This qualitative study conducted interviews with 11 Italian-Canadian immigrants from three different generations to explore how they cope with a crisis of meaning and takes into account themes surrounding culture, coping and time. Culture was present in how participants cope and make meaning of their crises, and religious coping was present for first-generation and older individuals.
Keywords: Immigration, Coping, Meaning, Crisis of Meaning, Italian, Culture